Gaya Kepemimpinan Kepala Yayasan Dalam Meningkatkan Kinerja Guru TK Nur Iman Palembang - Indrawari, Karliana; Hadi, Azwar (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Principals in Nur Iman Kindergarten are required to have a concern for the problems faced by students. The head of the foundation has functions as supervisors, leaders, teaching staff, and school administration. The purpose of this research is to find out the leadership style of the foundation head in improving teacher performance and education processing in Nur Iman Kindergarten, to find out the foundation head's achievements in improving teacher performance and educational processing in Nur Iman Kindergarten, and to find out the supporting factors and obstacles to the foundation head's leadership style in improving teacher performance and education processing in Nur Iman Kindergarten. The research method is field study research. Data collection techniques use observation, interviews and documentation. Data analysis techniques using miles and huberman, namely data reduction, data presentation, and data conclusions. The results showed that the head of the foundation had maximized the performance of teachers in Nur Iman Kindergarten.